Active Disturbance Rejection Based Approach for Velocity Control of a Three-Mass System - Do, Trong Hieu; Nguyen, Duy Vinh; Nguyen, Tung Lam (Old Journal, 2019)
The paper deals with a velocity control problem of a three-mass system. The equations of motion of the system with limited shaft stiffness and damping is derived via d’Alembert principle. Based on the system dynamics, an active disturbance rejection control is developed for the system via a support of an extended state observer. The designed process with systematic and simple approach shows better performances compared to PID control. Several numerical simulation scenarios are carried out to verify the robustness of the control.